(3LeGYGJ GdVZW GdjghOjI (B:s (3GdJfXje, GdOhQ hGdJCKjQ aj UfY GdbQGQ GdSjGSj ddhdGjGJ GdeJMOI GdCeQjcjI (B1945-1969 : (3OQGSI JGQjNjI (B/s - (3UHM,cQjes 1969-; (3CMeO, ceGd eXgQ,s 1937-2021 ((3HZOGO , GdYQGb (B: s (3HjJ GdMceI,s, 2009)
(3jJfGhd cJGH (B((3LeGYGJ GdVZW GdjghOjI (B: (3GdJfXje, GdOhQ hGdJCKjQ aj UfY GdbQGQ GdSjGSj ddhdGjGJ GdeJMOI GdCeQjcjI (B1945-1969) (3hGdPj bGe HJCdjag (B((3cQje UHM(B) (3aj MhGdj (B(2) (3eLdO ef GdbWY GdeJhSW ehVhY (B((3JGQjN LeGYGJ GdVZW GdjghOjI hJCKjQgG Ydi CeQjcG(B) (3eSJYQVG GdeMJhjGJ GdJGdjI(B: (3GdebOeI hJMdjd GdeUGOQ, GdaUd GdChd (B: (3OhQ GdYhGed GdJGQjNjI aj fThA LeGYGJ GdVZW GdjghOjI aj GdhdGjGJ GdeJMOI GdCeQjcjI MJi YGe (B1945(3e, hjTed (B: (3GdJWhQ GdJCQjNj dgLQGJ GdjghO Edi GdhdGjGJ GdeJMOI GdCeQjcjI, GdegGLQhf GdjghO heMGQHI GddGSGejI (B... (3EdN(B. (3GdaUd GdKGfj (B: (3JfXjeGJ LeGYGJ GdVZW GdjghOjI hJhRjYgG GdLZQGaj hWHjYI YedgG (B1945-1969(3e, hjTed (B: (3GdJfXjeGJ GdSjGSjI, GdJfXjeGJ GdGbJUGOjI hGdeGdjI (B... (3EdN(B.s
(3ENQGL hJfSjb hJUeje GdZdGa (B: (3YeQ YGOd YHGS(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3jJhGaQ HGdecJHI (B: (3eLdO (B1(3, (B2.s
Keywords: (3GdLeGYGJ GdVGZWIs -- (3GdhdGjGJ GdeJMOI GdCeQjcjIs; (3GdhdGjGJ GdeJMOI GdCeQjcjIs; (3ESQGFjds -- (3YdGbGJ NGQLjIs -- (3GdhdGjGJ GdeJMOI GdCeQjcjIs; (3GdhdGjGJ GdeJMOI GdCeQjcjIs -- (3YdGbGJ NGQLjIs -- (3ESQGFjds